2018
DOI: 10.1186/s12866-018-1195-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of STEC and other diarrheic E. coli isolated on CHROMagar™STEC at a tertiary referral hospital, Cape Town

Abstract: BackgroundShiga toxin producing E. coli (STEC) is an emerging zoonotic pathogen that can cause acute renal failure, especially in children. Clinical microbiology laboratories may fail to detect STEC and other diarrhoeic E. coli unless purposive rigorous screening procedures are followed using appropriate diagnostic technology; CHROMagar™STEC has rarely been used for isolation of African diarrhoeic E. coli hence characteristics of isolates on this medium are not yet fully understood. This study aimed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
6
8
1
4
Order By: Relevance
“…Previous studies evaluating CHROMagar STEC have focused on the non-O157 serogroups most likely to cause severe symptoms, STEC O26, O103, O111, O121, O145 and O45, referred to in the literature as the ‘top six’; while others have included a wider range of STEC serogroups [8–11, 17, 18]. With the exception of Wylie et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluating CHROMagar STEC have focused on the non-O157 serogroups most likely to cause severe symptoms, STEC O26, O103, O111, O121, O145 and O45, referred to in the literature as the ‘top six’; while others have included a wider range of STEC serogroups [8–11, 17, 18]. With the exception of Wylie et al .…”
Section: Discussionmentioning
confidence: 99%
“…All 106 isolates of STEC that grew on CHROMagar STEC had the ter gene cassette, which in STEC O157:H7 comprises eight genes terZ, terA, terB, terC, terD, terE, terF and terW [19, 20]. Correlation of growth of STEC on CHROMagar STEC with the presence of the ter gene cassette encoding resistance to tellurite is well documented in the literature [8–11, 17, 18]. Successful detection of STEC in a complex background requires an agar medium that suppresses the growth of background micro-organisms with minimal suppression of target STECs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genome analyses indicated that the ter operons and their carrier elements are highly conserved among STEC strains belonging to the major serotypes (Ogura et al, 2009;Lorenz et al, 2017). Some STEC isolates, such as STEC O104:H4 and O178:H19, and non-STEC E. coli isolates also carry ter operons and/or show significant tellurite resistance (Orth et al, 2007;Gouali et al, 2013;Miko et al, 2014;Ferdous et al, 2015;Verhaegen et al, 2015;Kalule et al, 2018;Nguyen et al, 2021). A uropathogenic E. coli isolate was found to carry the ter operon on a large conjugative plasmid (Soltys et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing (NGS) and bioinformatics, metagenomics study becomes more convenient, efficient, cost-effective and overcome the problem of which most of the microorganism cannot be isolated and maintained in pure culture 12 , 13 . Many metagenomic studies of arthropods including mosquito 14 , tick 15 , assassin bugs 16 , tsetse flies 17 as well as common bed bugs 18 had used the sequencing of 16S rRNA gene to characterize the microbiota. However, the microbiome of tropical bed bugs, C. hemipterus , remains mostly unexplored, and the application of high-throughput sequencing in the characterization of bacteria community in tropical bed bugs is not available.…”
Section: Introductionmentioning
confidence: 99%